First results of distal gastric shunting with one anastomosis in patients, suffering morbid obesity - A. S. Lavryk; A. Yu. Zgonnyk; O. A. Lavryk; R. I. Vynogradov (Клінічна хірургія, 2019)
Objective. To study a metabolic effect of distal gastric shunting with one anastomosis in patients, suffering morbid obesity (MO).